Consumer decision making process in shopping for halal food in Malaysia. - Abdul, Mohani; Ismail, Hashanah; Hashim, Haslina; Johari, Juliana (2009)
This paper reports on the results obtained from quantitative and qualitative data on consumer decision making process in shopping for halal food. A total of 213 questionnaires were returned by respondents, confirming that our respondents who are concerning about the "halal" logo are also concerning about the ingredients used. The study also confirms that there is a significant relationship between respondents'religion and their perceptions towards halal logo and ingredients. While the qualitative data from a focus group interview on how Muslim consumers shop for halal food shows that there is a need for assurance that food to be purchased is halal, implying the presence of risk and uncertainty when making purchase considerations. Using the audit risk framework in conventional assurance services, the study finds that assurance is sought in relation to the halalness of business premise, halalness of product, and assurance from environmental elements such as the halal logo displayed.